Impact of Proton–Proton Collisions on the Cosmic-Ray Spectrum in Giant Clouds - Hao-Ran Ge; Ruo-Yu Liu (Universe)
Gamma-ray production by proton–proton (<semantics>pp</semantics>) inelastic collisions plays an important role in searching for cosmic-ray (CR) accelerators. Understanding the pionic gamma-ray production associated with giant molecular/atomic clouds is thus crucial to identify this process. In this work, we study the feedback of the pionic gamma-ray production to the CR distribution, by considering collision-induced energy loss on cosmic-ray protons in the dense core region of molecular clouds (MCs). We try to introduce a Monte Carlo simulation framework to quantify this effect, and present a detailed analysis to evaluate how <semantics>pp</semantics> collisions harden the cosmic-ray proton spectrum and the resulting gamma-ray spectrum in giant clouds.